Zapożyczenia w twórczości Adama Mickiewicza z lat 1818-1828 = Foreign words in Adam Mickiewicz's output from the years 1818-1828 - Tyszka, Sylwia (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
This article presents the results of Mickiewicz's works' analysis from the years 1818-1828. The study was carried out in order to answer the following questions: did the writer use words borrowed from other languages in his works? If so, from which languages and how often did he do that? What was his attitude towards loanwords and language purism? The paper shows popular foreign words in the Polish language in the 19th century and those used by the writer for the sake of artistic stylization, quite often conferring new meanings onto them. The article also presents words which were being adapted in the times of Mickiewicz.
Keywords: Mickiewicz, Adam (1798-1855); wyrazy obce; literatura - 19 w.; literature; foreign words; 19 w.